2017
DOI: 10.1371/journal.pone.0183765
|View full text |Cite
|
Sign up to set email alerts
|

Association between statin use, the vaginal microbiome, and Gardnerella vaginalis vaginolysin-mediated cytotoxicity

Abstract: BackgroundBacterial vaginosis (BV) is the leading dysbiosis of the vaginal microbiome. The pathways leading towards the development of BV are not well understood. Gardnerella vaginalis is frequently associated with BV. G. vaginalis produces the cholesterol-dependent cytolysin (CDC), vaginolysin, which can lyse a variety of human cells and is thought to play a role in pathogenesis. Because membrane cholesterol is required for vaginolysin to function, and because HMG-CoA reductase inhibitors (statins) affect not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
(52 reference statements)
0
20
0
Order By: Relevance
“…VLY mediates lactate dehydrogenase release only when exposed to the basolateral face. Previous studies indicate that VLY induces cytopathogenic changes in vaginal epithelial cells cultured as monolayers and lactate dehydrogenase (LDH) release (64). We extended these findings through the analysis of cytotoxicity in a threedimensional model of the vaginal epithelium.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…VLY mediates lactate dehydrogenase release only when exposed to the basolateral face. Previous studies indicate that VLY induces cytopathogenic changes in vaginal epithelial cells cultured as monolayers and lactate dehydrogenase (LDH) release (64). We extended these findings through the analysis of cytotoxicity in a threedimensional model of the vaginal epithelium.…”
Section: Resultsmentioning
confidence: 70%
“…Expression and purification of recombinant VLY. E. coli strain BL21(DE3) CodonPlus/pRIPL (Agilent technologies) was previously transformed with an isopropyl-␤-D-thiogalactopyranoside (IPTG)-inducible, vlycontaining pET32XT vector (64). One-liter cultures were grown to exponential phase (optical density at 600 nm [OD 600 ] of 0.5) and induced with 1 mM IPTG for 2 h, and the bacteria were collected by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned, CD59 is overexpressed in many types of tumors, including breast cancer. 49 Abdelmaksoud et al 50 observed a dose-dependent reduction of G. vaginalis and normalizing the level of Lactobacillus spp. in vaginal flora after treatment with statins, known as lipid-decreasing mediators.…”
Section: Potential Role Of Microbiome In Endometrial Cancer Initiatiomentioning
confidence: 98%
“…Statins are reported to have a great effect on vaginal microbiome via reduced proportions of Gardnerella vaginalis and increased proportions of beneficial lactobacilli. 49 In addition, statins diminished the risk of infections in patients with type 2 diabetes. 50 Inversely, in patients with dementia statin, therapy was associated with increased risk of infection.…”
Section: Infectionmentioning
confidence: 99%